The PENGEMBANGAN MEDIA PEMBELAJARAN PUZZLE MODEL TETRIS PECAHAN UNTUK MENINGKATKAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS IV SDIT BINA CENDEKIA - Tintin Rustini; Muhamad Sofian Hadi (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Math lessons, especially fractions, often pose difficulties for some students at the primary school level. Various learning methods and media are needed to overcome these challenges. One of the interesting learning media is the Tetris puzzle model. This study aims to evaluate the effectiveness of using Tetris fraction puzzle media in improving the math learning outcomes of fourth grade students at SDIT Bina Cendekia. This research uses a qualitative approach to accurately describe symptoms or phenomena. The subjects of this study were 25 fourth grade students of SDIT Bina Cendekia. The research took place during March 2023 and involved various data collection methods, including classroom observations, interviews with teachers and students, and documentation of learning activities. Data were analyzed in a number of stages, including mapping, thematic analysis, and interpretation. The results showed that the use of Tetris fraction puzzle learning media significantly improved student achievement. Students who initially had difficulty understanding fraction math lessons admitted that it was easier to understand the teacher's explanation and do the assignments. During the summative test, the average student's fraction math score increased significantly.